Islamic Republic of Afghanistan : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2016)
The Ex Post Assessment aims to provide a frank review of progress during the 2006 and 2011 programs, and a forward-looking assessment that takes into account lessons learned. It begins by providing the background and context for the two programs. It then discusses their overall objectives, how the programs were designed to achieve these objectives, and program performance. After outlining the key issues, it concludes with some lessons, including for Afghanistan's future engagement with the IMF. Since late 2001, after NATO forces toppled the Taliban, the country received unprecedented support from the donor community in the context of two IMF-supported programs.